Comparison of simulated structural deformation with experimental results after Wingspan stenting. (August 2014) - Fujimoto, Motoaki; Shobayashi, Yasuhiro; Tateshima, Satoshi; Sudo, Ryo; Tanishita, Kazuo; Viñuela, Fernando
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: Biomechanical stress distribution correlates with the biological responses after stenting. Computational analyses have contributed to the optimization of stent geometry. In particular, structural analysis based on pre-operative angiography can be used to predict the stent–artery interaction before endovascular treatments. However, the simulated results need to be validated. In this report, we compared the simulated arterial structure with post-operative images after an intracranial Wingspan stent. Methods: A Wingspan stent was deployed at a slightly curved ascending pharyngeal artery (APA) in the swine. Using a finite element method (FEM), the configuration after stenting was simulated and quantitatively compared with post-procedural 3D angiography. Results: The finite element analysis demonstrated arterial straightening after stenting. The simulated images were similar to the experimental results with respect to the curvature index of the center line and the cross-sectional areas. Conclusion: We assessed the simulated structural deformation after Wingspan stenting, by comparison with experimental results.